Respon Guru-Guru MGMP IPA Bulukumba sebelum Pelatihan Pembuatan Eco Enzyme menjadi Eco Soap - Nurhayani H. Muhiddin; Rifda Nur Hikmahwati Arif; Salma Samputri; Ramlawati Ramlawati; Ahmad Syakur (JKM: Jurnal Kemitraan Masyarakat, 2024)
Natural Science (IPA) teachers in some schools still experience limitations in understanding and teaching biotechnology applications, especially in making eco enzyme into eco soap. Eco soap is an innovation in the world of biotechnology that combines environmentally friendly principles with the sustainability of soap production. However, many science teachers are not yet fully familiar with this concept and have not been able to provide students with a deep understanding. The response results showed that the response of MGMP Science teachers in Bulukumba about eco enzyme and eco soap, only a few know about eco enzyme and eco soap and most do not know or about 50% more who do not know about eco enzyme and eco soap. This means that the average MGMP Science teacher in Bulukumba does not know about eco enzyme and eco soap before training.